Perubahan Bervariasi dalam Transformasi Novel Kokuhaku ke Film - Ningsih, Eka Fitra; Meilantari, Ni Luh Gede (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2024)
This research is entitled "Variety Changes in the Transformation of Kokuhaku Novel into Film". This research aims to describe the various changes that occur in the transformation of Kokuhaku's novel into film, so that readers and viewers can see the comparison of these two works objectively. The data sources for this research are the novel Kokuhaku by Minato Kanae and the film Kokuhaku directed by Tetsuya Nakashima. Kokuhaku is the debut novel of the famous Japanese writer Minato Kanae in the psychological thriller genre. Both the novel and the film of Kokuhaku have won awards that show the public's appreciation for these two literary works. The research method used is descriptive qualitative method. The theory used in this research is the theory of ecranization by Eneste. The results of this study indicate that there are various changes in the transformation of Kokuhaku's novel into the film, including that important objects in the story are highlighted, and some parts are made to be more dramatic. These changes are due to the difference in media between the two literary works. The purpose of these changes is to make it easier for the audience to remember important things in the storyline and identify the characters in the Kokuhaku film.